2014
DOI: 10.1099/mic.0.080366-0
|View full text |Cite
|
Sign up to set email alerts
|

Localization and expression of the Bacillus subtilis dl-endopeptidase LytF are influenced by mutations in LTA synthases and glycolipid anchor synthetic enzymes

Abstract: Bacillus subtilis LytF plays a principal role in cell separation through its localization at the septa and poles on the vegetative cell surface. In this study, we found that a mutation in a major lipoteichoic acid (LTA) synthase gene -ltaS -results in a considerable reduction in the s D -dependent transcription of lytF. The lytF transcription was also reduced in mutants that affected glycolipid anchor biosynthesis. Immunofluorescence microscopy revealed that both the numbers of cells expressing LytF and the Ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 50 publications
(72 reference statements)
1
19
0
Order By: Relevance
“…In addition to these phenotypes, a quadruple ltaS homolog mutant shows a loss of LTA (7), an aberrant twisted morphology, slower growth (6), and reduced adsorption of rare earth elements (8,9). Moreover, we reported that D -dependent transcription of lytF, which encodes a DL-endopeptidase that functions in cell separation, is reduced in an ltaS mutant and is nearly absent in multiple mutants of ltaS and its homologs (10). Interestingly, we also found that lytF transcription was repressed in tagO-null mutant cells, which lack WTA.…”
mentioning
confidence: 88%
See 4 more Smart Citations
“…In addition to these phenotypes, a quadruple ltaS homolog mutant shows a loss of LTA (7), an aberrant twisted morphology, slower growth (6), and reduced adsorption of rare earth elements (8,9). Moreover, we reported that D -dependent transcription of lytF, which encodes a DL-endopeptidase that functions in cell separation, is reduced in an ltaS mutant and is nearly absent in multiple mutants of ltaS and its homologs (10). Interestingly, we also found that lytF transcription was repressed in tagO-null mutant cells, which lack WTA.…”
mentioning
confidence: 88%
“…The sample preparation for immunofluorescence microscopy (IFM) was described previously (10,23) and used with minor modifications, as follows. An anti-DYKDDDDK tag monoclonal antibody (1:400; Wako Pure Chemical Industries) was used as the primary antibody, and an Alexa Fluor 555 F(ab=) 2 fragment of goat anti-mouse IgG (HϩL) (1:1,200; Life Technologies) was used as the secondary antibody.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations